PENGARUH PEMBIAYAAN MURABAHAH, EFISIENSI OPERASIONAL (BOPO) DAN PEMBIAYAAN BERMASALAH (NPF) TERHADAP PROFITABILITAS (ROA) PADA BANK UMUM SYARIAH PERIODE 2015-2019 - Indah Marlina; Nana Diana (JURNAL EKOMBIS, 2021)
This research aimed to examine the effects of Murabahah Financing, Operational Efficiency (BOPO) and Non Performing Financing (NPF) on Profitability (ROA) in Islamic Commercial Banks for the 2015-2019 Period. The sampling technique uses porpusive sampling. Methods of data analysis using quantitative descriptive and verification. The population in the study were all 14 Islamic Commercial Banks for the 2015-2019 Period. There are 11 Islamic Commercial Banks that meet the criteria. The statistical processing method uses SPSS v.21. The result showed that Murabahah financing has no significant effect on profitability. Operational Efficiency (BOPO) has a negative and significant effect on profitability (ROA).  Non Performing Financing (NPF) has a negative and significant effect on profitability (ROA). Murabahah Financing, Operational Efficiency (BOPO) and Non Performing Financing (NPF) together have a positive and significant effect on profitability (ROA).Keywords: Murabahah Financing, Operational Effeciency (BOPO), Non Performing Financing (NPF), Profitability (ROA)